COVID-19 testing: Essential for tracking infection and helping authority to overcome the challenges of spread - Piryani, Rano Mal; Piryani, Suneel; Piryani, Shomeeta; Dangal, Ganesh; Huq, Muzaherul; Shakya, Dhana Ratna (Journal of Chitwan Medical College, 2020)
COVID-19 is mainly transmitted through droplet infection and spread very fast compared to SARS-CoV and MERS-CoV. For the countries, it is important to know at what stage the COVID-19 epidemic is? So, as to take appropriate steps to contain the epidemic. This will only be known by testing the suspects and contacts of confirmed cases. If there is poor testing, then most of the infected people may remain undetected, however they could spread the virus to hundreds of other people and potential contacts, which could not be known and quarantined in time continuing the spread. If there is quality assured, highly sensitive and specific testing along with adequate isolation and quarantine, then the spread will be limited. There are two types of tests available for COVID-19: the tests directly detecting the viral ribonucleic acid (RNA) collected in nasopharyngeal or throat swabs, and tests detecting antibodies from the blood sample. At this point in time, the polymerase chain reaction (PCR) tests are used for confirmation of the disease while antibodies tests may provide information regarding the prevalence of infection. World Health Organization advices the countries to increase the testing and get to know the level of epidemic and act accordingly for containment of infection.